2016
DOI: 10.1186/s12974-016-0754-9
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces morphine tolerance by inhibiting microglial-mediated neuroinflammation

Abstract: BackgroundTolerance seriously impedes the application of morphine in clinical medicine. Thus, it is necessary to investigate the exact mechanisms and efficient treatment. Microglial activation and neuroinflammation in the spinal cord are thought to play pivotal roles on the genesis and maintaining of morphine tolerance. Activation of adenosine monophosphate-activated kinase (AMPK) has been associated with the inhibition of inflammatory nociception. Metformin, a biguanide class of antidiabetic drugs and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 44 publications
2
62
2
Order By: Relevance
“…Morphine has been shown to induce autophagy in the neuroblastoma cell line [52], in bone marrow-derived macrophages [64], and in the mice hippocampus [2,65,52,43]. Our previous studies have also shown that morphine exposure resulted in synaptic injury in the hippocampal neurons and that this was mediated via the ER stress-autophagy axis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Morphine has been shown to induce autophagy in the neuroblastoma cell line [52], in bone marrow-derived macrophages [64], and in the mice hippocampus [2,65,52,43]. Our previous studies have also shown that morphine exposure resulted in synaptic injury in the hippocampal neurons and that this was mediated via the ER stress-autophagy axis [43].…”
Section: Discussionmentioning
confidence: 99%
“…During the past two decades, a number of associated intracellular signaling cascades, including the mitogen-activated protein kinase (MAPK) signaling cascades have been described. MAPKs may be activated by morphine via opioid receptors, and their activation has been observed in synaptic plasticity and addiction (8)(9)(10)(11)(12)(13)(14). In vivo, a role of MAPKs in opioid analgesia and sedation has additionally been proposed (15).…”
Section: Introductionmentioning
confidence: 99%
“…All these factors may affect the functional recovery by limiting axonal outgrowth and preventing reformation of functional synapses. 27 Exosome administration has been shown to attenuatemicroglial-mediated neuroinflammation and reduce neuronal damage in a SCI model 28 .Furthermore, it was reported that exosomeadministration ameliorated insulin resistance by inhibiting oxidative stress in adipocytes 29 . Pandeyetal have demonstrated that exosome treatment inhibited iNOS signaling in experimental model of colitis 30 .…”
Section: Hypothesis Of the Role Of Exosome In Inos/txnip/nlrp3 Inflammentioning
confidence: 99%